Evidence for late winter biogeochemical connectivity in permafrost soils - Catherine Hirst; Arthur Monhonval; Elisabeth Mauclet; Maxime Thomas; Maëlle Villani; Justin Ledman; Edward. A. G. Schuur; Sophie Opfergelt (Communications Earth & Environment, 2023)
Longer periods of biogeochemical connectivity in soil porewaters with a deeper active layer suggest early organic carbon transport during the dormant season, according to silicon isotope compositions of permafrost soil porewaters in Alaska.